Perlindungan Hukum Hak Korban Tindak Pidana Kekerasan Seksual di Perguruan Tinggi - Devika Claretta Angesti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Sexual violence is all acts carried out with the aim of obtaining sexual acts or other actions directed at someone's sexuality of their relationship status with the victim. This paper will formulate forms of victims' rights and efforts that can be made by victims if their rights are not fulfilled as well as legal protection for victims of sexual violence. The formulation of the problem of writing includes the form of rights of victims of sexual violence that often occurs in the university as well as the rights of legal protection for victims of criminal acts of sexual violence based on the TPKS. Permendikbud aims to guarantee protection for victims by guaranteeing the rights of victims. In the end, the existence of this regulation is intended to foster a campus life. TPKS seeks to prevent and recover victims as a fulfillment of the rights of victims of violence. In this case, it aims to prevent all forms of sexual violence, create an environment without sexual violence and ensure the non-recurrence of sexual violence. These regulations ultimately fulfill the rights of victims. Thus, the presence of the Minister of Education and Culture and the TPKS Law are legal protection and legal certainty for victims of violence by involving stakeholders in order to achieve the objectives of handling, protecting and recovering victims. The type of research used in this paper is normative juridical. The results of the discussion are presented descriptively.